Fabrication and characterization of polyimide/ polyethersulfone-fumed silica mixed matrix membrane for gas separation - A. F. Ismail; T. D. Kusworo (Dept. of Chemical Engineering, Diponegoro University, 2007)
This study is performed primarily to investigate the feasibility of fumed silica as inorganic material towards gas separation performance of mixed matrix membrane. In this study, polyimide/ polyethersulfone (PES)-fumed silica mixed matrix membrane were casted using dry/wet technique. The result from the FESEM, DSC and FTIR analysis confirmed that the structure and physical properties of membrane is influenced by inorganic filler. FESEM`s cross-section view indicated good compatibility between polymer and fumed silica for all of range fumed silica used in this study. The gas separation performance of the mixed matrix membrane with fumed silica were relatively higher compared to that of the neat PI/PES membrane. PI/PES-fumed silica 5 wt% yielded significant selectivity enhancement of 7.21 and 40.47 for O2/N2, and CO2/CH4, respectively.Keywords: gas separation membrane, mixed matrix membrane, silica